2018
DOI: 10.1007/s11010-018-3378-9
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect on endothelial surface layer damage of Fusu agent in LPS-induced acute lung injury in rats

Abstract: Acute lung injury (ALI) is one of major causes of morbidity and mortality in intensive care. In pathophysiological events of ALI, endothelial surface layer (ESL) injury can result in capillary leakage as the initial event. The "Fusu agent", a traditional Chinese medicine, can inhibit inflammatory factors, attenuate lung capillary leak as seen in our previous study. This study was aimed to explore the molecular mechanism of Fusu agent treatment with ALI. Consistent with previous studies, we found that Fusu agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Through animal experiments, it was confirmed that the TCM resuscitation mixture could improve the pathological changes of lung tissue in rats, inhibit the expression of heparanase in the plasma of acute lung injury caused by sepsis, and reduce the release of inflammatory factors. This shows that the Fusu mixture has a certain effect on sepsis-induced ARDS, [ 7 ] which provides basic evidence for the clinical treatment of the Fusu mixture.…”
Section: Introductionmentioning
confidence: 89%
“…Through animal experiments, it was confirmed that the TCM resuscitation mixture could improve the pathological changes of lung tissue in rats, inhibit the expression of heparanase in the plasma of acute lung injury caused by sepsis, and reduce the release of inflammatory factors. This shows that the Fusu mixture has a certain effect on sepsis-induced ARDS, [ 7 ] which provides basic evidence for the clinical treatment of the Fusu mixture.…”
Section: Introductionmentioning
confidence: 89%